Observations and simulations of cloud thermodynamic phase over the southern ocean - Huang, Yi (Monash University, 2017)
A climatology of the structure of the low-altitude cloud field over the Southern Ocean (SO, 40-65S, 100-160E) is constructed with CloudSat products for ice and liquid water. The results reveal that the CloudSat climatology produces a roughly uniform cloud field between heights of ~750-2250 m across the extent of the domain with little seasonal variation. The vast majority of these clouds reside in the temperature range of 0 to -20C, where the cloud profiling radar (CPR) on CloudSat cannot determine the thermodynamic phase. CloudSat is also unable to make reliable observations in the lowest kilometer due to the ground clutter contamination, yet the few direct observations suggest that boundary layer depth is often below 1 km and cloudy. A climatology of the cloud thermodynamic phase over the SO has been constructed with the A-Train merged data product DARDAR-MASK. Results are consistent with the CloudSat climatology, showing that low-elevation clouds (< 1 km) with little seasonal cycle dominate the region. Such clouds are also problematic for the DARDAR-MASK due to the limitation of CPR and the CALIOP lidar on CALIPSO commonly suffering from heavy extinction. A comparison between the climatology derived from CALIPSO, the DARDAR-MASK and MODIS highlights the extensive existence of supercooled liquid water (SLW) over the SO, particularly during summer. The DARDAR-MASK recorded substantially more ice and mixed phase at cloud-tops, whereas MODIS observed significantly more low-level/warm clouds. Moving beyond the cloud-top, the DARDAR-MASK finds ice to be dominant above 1 km and uncertain class to be frequent below 1km. The A-Train satellite observations have also been used to evaluate the Weather Research and Forecasting (WRFV3.3.1) NWP Model in simulating the postfrontal clouds over Tasmania and the SO. Results show that the simulations are reasonably capable of capturing the macrostructure and thermodynamic phase composition of the frontal convective clouds, the post-frontal stratocumulus clouds and to a lesser extent, the mid-top stratiform SLW clouds. The simulations have great difficulties capturing the widespread marine boundary layer (BL) clouds. The simulated thermodynamic phase, cloud-top and column integrated properties are sensitive the microphysical scheme and to a lower degree, vertical resolution. The simulations are only marginally sensitive to the planetary boundary layer schemes. The cloud condensation nuclei concentration has a large impact on the simulated liquid water path, particularly for marine BL clouds. Two selected flights from an A-Train validation project over the SO are studied. Preliminary analysis suggests that acceptable agreement is achieved between the A-Train observations and aircraft measurements in terms of the detection of cloud macrostructure and spatial distributions. However, significant challenges remain in characterization of the cloud microphysical properties. The CPR on CloudSat solely is inadequate to determine the cloud thermodynamic phase and has limitation in detecting optically thin liquid water clouds. These findings are consistent with the climatologies. The results in this thesis highlight the enormous challenge that remains in better defining the energy and water budget over the SO. It supports the call for a long-term dedicated field campaign with ground-based radar-lidar observation and in-situ microphysics measurements.